The studio SOS book : solutions and techniques for the project recording studio - White, Paul, 1949- (Sound on sound., 2013)
Professional studio design is a specialized science, with more than a touch of ""black magic"" thrown in. Over the past few years, Sound on Sound magazine has made one trip each month to a reader's studio. These visits have demonstrated that it is fairly simple to make a huge improvement to an untreated project-studio room, without spending a fortune. However, they've also proven that beginners' attempts at DIY acoustic treatments often cause more problems than they solve. Utilizing knowledge from dozens of visits to readers' home and project studios, the SOS team imparts easy.